2019
DOI: 10.1093/rb/rbz021
|View full text |Cite
|
Sign up to set email alerts
|

Cell and biomaterial-based approaches to uterus regeneration

Abstract: Asherman’s syndrome (AS) is an endometrial disorder in which intrauterine adhesions crowd the uterine cavity and wall. The fibrotic adhesions are primarily the result of invasive uterine procedures that usually involve the insertion of surgical equipment into the uterus. This syndrome is accompanied by a number of clinical manifestations, including irregular or painful menstruation and infertility. The most prevalent treatment is hysteroscopy, which involves the physical removal of the fibrous strands. Within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 45 publications
0
30
0
Order By: Relevance
“…Biomaterials provide structural and mechanical support for tissue repair by helping to restore the architecture and functionality of the wounded tissues. They may also partially mimic native environment by inducing physicochemical changes and simulating changes of growth factors, signaling molecules and extracellular vesicles like cellular materials Liu et al, 2019a). However, it is insufficient to simply use scaffold biomaterial for repairing large uterus defects (Xin et al, 2019).…”
Section: Cell-scaffold Interface-based Endometrium Regenerationmentioning
confidence: 99%
See 1 more Smart Citation
“…Biomaterials provide structural and mechanical support for tissue repair by helping to restore the architecture and functionality of the wounded tissues. They may also partially mimic native environment by inducing physicochemical changes and simulating changes of growth factors, signaling molecules and extracellular vesicles like cellular materials Liu et al, 2019a). However, it is insufficient to simply use scaffold biomaterial for repairing large uterus defects (Xin et al, 2019).…”
Section: Cell-scaffold Interface-based Endometrium Regenerationmentioning
confidence: 99%
“…Biomaterials can release drugs, growth factors, small molecules and other bioactive compounds in a controlled style, with or without cell loading and modification. Recent researches have shown that, in addition to traditional biomaterial based uterus regeneration, combination and modification of cells and biomaterials, such as cell sheets, cell-scaffold interfaces, surface-functionalized scaffolds and decellularization of biological tissues may also display functional or structural advantages and repair injured uterus to different extents by inducing biomimetic changes and recreating regenerative microenvironment (Liu et al, 2019a). Therefore, we comprehensively reviewed current advances in the biological interactions and applications of different types of biomimetic endometrium and uterus scaffolds for female infertility treatment and compared their potential therapeutic effects in this review (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that, in addition to traditional regeneration of uterus promoted by the biomaterials, their combination with modified cells, e.g., cell layers, intercellular boundaries, surface-functionalized frameworks and decellularized biological tissue, may also exhibit functional or structural advantages. These approaches may provide recovery of altered uterine structures to some degree by inducing biomimetic changes and restoring the regenerative microenvironment [16,17].…”
Section: Endometrium Regeneration Using Surface-functionalized Hydrogelsmentioning
confidence: 99%
“…Owing to their ability to proliferate and differentiate into a range of cell types, stem cells are promising tools for cell-based therapeutic approaches, [7] with endometrial stem/progenitor cells, in particular, having the potential to facilitate endometrial regeneration in those affected by thin endometrium. [7,8] The transplantation of bone marrow-derived stem cells (BMSCs) and adipose-derived stem cells (ADSCs) has been studied as Thin endometrium is a primary cause of failed embryo transfer, resulting in long-term infertility and negative family outcomes. While hormonal treatments have greatly improved fertility results for some women, these responses remain unsatisfactory due to damage and infection of the complex endometrial microenvironment.…”
Section: Introductionmentioning
confidence: 99%